Coercion to destroy other people’s money between sharia Jordan’s Civil Code: Comparative study - Shwayat, Ammar Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2021)
This research deals with the issue of coercion to destroy the money of others in Islamic sharia and Jordanian civil law and the importance of this research is evident by showing the picture of the truth of the jurisprudential issues based on this type of coercion. And the sharia ruling in these pictures. And the problem of the research revolved around the sayings of scholars about the reality of coercion. The main objective of the study is to make a comparison between sharia and Jordanian civil law in this matter. As for the key words included in the research. They Are: coercion money destruction of money. Immoral coercion. And unresolved coercion. As for relying in this study on three main approaches. Namely: 1. the inductive approach for all the scientific subject: by referring to what I have available to me from language and fundamentals books. Branches and jurisprudential rules. And books on jurisprudential and law. 2 the analytical method for this available research material by presenting the sayings of scholars in Islamic law and Jordanian civil law 3. The comparative approach by presenting the saying of the four schools of thought and the Jordanian civil law 4 the attribution of the Quran to their place in the noble Quran and the output of the hadiths based on the two sahib al – Bukhari. Then the four Sunnah again and attributing the effects contained in this study to their books and Sayers with judging.to achieve this topic. I divided my research into two coats. The first requirement: clarifies the definition of language and law. the pillars and conditions of coercion. types of coercion. recourse and non – recourse coercion. Moral coercion. And the evidence for the existence of coercion from the holy Quran and the Sunnah. As for the second requirement. It death with the effect of coercion on destroying the money of others in Islamic sharia and Jordanian civil law in coercion.